Effect of temperature and humidity index (THI) on the physiological responses of grazing dairy cows - Valdivia, J. C.; Reyes, J. J.; Valdés, G. R. (Cuban Journal of Agricultural Science, 2021)
The evaluation was performed with 25 cows from dairy 17, belonging to Dos Ríos enterprise, in order to assess the relation between the temperature and humidity index, rectal temperature and respiratory rate. The information was taken at three times of the day: morning, midday and afternoon. The results showed that in the morning the cows are in a thermo neutral zone (temperature and humidity index 69.59), while at midday they are under medium heat stress (THI 79.61), and in the afternoon under severe stress (THI 91.69). Under severe heat stress, the rectal temperature of pregnant lactating cows increased (P = 0.0136) by 0.28 ºC with respect to the rectal temperature of non-pregnant lactating cows. The respiratory rate was not affected by the light temperature and humidity index. But in the moderate stress, pregnant cows showed higher (P = 0.0003) respiratory rates of 1.9 and 2.0 % in relation to non-pregnant cows for moderate and severe stress, respectively. The physiological response to the temperature and humidity index, according to the milking group, showed that the high production group had higher rectal temperature values (P = 0.0003) in 0.16 and 0.21 oC and the respiratory rate increased (P = 0.0024) in 9.21 and 7.89 % in relation to the average group, for moderate and severe stress, respectively. Under the conditions of this study, at midday and afternoon, the animals are under moderate and severe stress, respectively, conditions that affect more the lactating pregnant animals and the open cows or the highest production group. Key words: rectal temperature, respiratory rate, milk production